Primary diffuse large B-cell tumor of the uterus: a case report - Zhang, Zhiming; Yang, Qing (Frontiers in Medicine, 2023)
Primary diffuse large B-cell tumor of the uterus is a rare clinical condition with a similar clinical presentation to gynecologic tumors and is easily misdiagnosed. We report a case of a postmenopausal woman who presented with pelvic mass. Her ultrasound and MRI examinations suggested diffuse enlargement of the uterus, leading us to consider the diagnosis of lymphoma. The histological examination of the uterine mass confirmed the diagnosis of diffuse large B-cell lymphoma. The patient received 6 cycles of chemotherapy with R-CHOP (rituximab, cyclophosphamide, doxorubicin, vincristine and prednisone) and 2 cycles of consolidation therapy with R (rituximab). After treatment, the patient's uterus was significantly smaller than before and there was no sign of a recurrence.